O Agronegócio e o problema do trabalho infantil - Marin, Joel Orlando Bevilaqua [UNESP] (FapUNIFESP (SciELO), 2010)
This article attempts to identify and analyze the motives that led several sectors of agro-business to engage in the struggle for the eradication of child labor in Brazil, as launched by international organizations for the defense of children's and adolescents' rights. It is our hypothesis that economic globalization and the internationalization of children's rights have given visibility to the problem of child labor, thus demanding the mobilization of entrepreneurial sectors linked to agro-business productive chains in Brazil. The article is divided into four inter-related sections. In the first one, we attempt to provide evidence for the interference of social and labor problems within the ambit of the economic activities of the agro-business sector, within the current context of globalization. This is followed by a study of major UN, UNICEF and ILO investments to internalize children's rights and policies to combat child labor, giving salience to their repercussions in Brazil. In the third section, we analyze strategies adopted by firms linked to agro-business with the purpose of avoiding the use of child labor within their productive chains. Finally, we seek to understand the motivations that have led agro-businessmen to take part in the struggle against child labor. We conclude that firms linked to agro-business took up the project of combating child labor in virtue of the internationalization of children and adolescents' rights, the inclusion of social issues in international markets, the intensification of the fiscalization of public power, the growth of action around entrepreneurial social responsibility and increased consumer consciousness.
Agrobusiness and the problem of child labor
Keywords: Agribusiness; Child labor; Children's rights; Exploitation; Globalization